Exploring the Genetic Conception of Obesity via the Dual Role of FoxO - Behl, Tapan (Int J Mol Sci, 2021)
Obesity or overweight are not superficial problems, constituting a pressing issue. The obesity index has almost tripled since 1975, which is an alarming state. Most of the individuals are currently becoming overweight or have inappropriate body mass index (BMI) conditions. Obesity is characterized by increased fat accumulation and thus poses a higher health risk. There is increased size and volume of fat cells in the body, which usually accounts for obesity. Many investigations have been carried out in this area, such as behavioral improvements, dietary changes, chemical involvements, etc., but presently no such goals are established to manage these health concerns. Based on previous literature reports and our interpretation, the current review indicates the involvement of various transcriptional and transporter functions in modifying the above-mentioned health conditions. Various transcriptional factors such as Forkhead box O1 (FoxO1) impart a significant effect on the physiology and pathology of metabolic dysfunction such as obesity. FoxO1 plays a dual role whether in the progression or suppression of metabolic processes depending on its targets. Thus, in the current study, will be discussed the dual role of FoxO1 in metabolic conditions (such as obesity), also summarizing the role of various other transcriptional factors involved in obesity.